The future of DAOs in finance: In need of legal status - Ellen Naudts (European Central Bank (ECB), 2023)
Despite the crypto-market crash in the spring of 2022 and the collapse of FTX in November 2022, decentralised finance (DeFi) proponents are still predicting that DeFi may soon go mainstream. As well as the increasing involvement of regulated financial institutions in the DeFi area, the incipient presence of regulatory, supervisory and oversight frameworks may lead to more mainstream acceptance of DeFi. Many DeFi projects are structured in the form of a decentralised autonomous organisation (DAO), a virtual organisation built and run on code and blockchain technology. As this new DAO corporate structure has benefits appropriate for the era of digitalisation and decentralisation, the number of DAOs is growing. However, most countries around the globe do not yet have in place a specific legal regime for DAOs. Until now, DAOs have been operating outside of regulatory financial frameworks, even though they may perform functions that are similar to regulated financial institutions or market infrastructures. The legal characterisation of DAOs depends on national laws that may or may not apply, depending on how the DAO itself is actually set up and on court judgements. This paper introduces the DAO structure and how it relates to other methods of organisation in finance. The paper lists use cases and describes the benefits and drawbacks of the DAO structure, taking a closer look at (inter)national regulatory frameworks, guidelines and recommendations in order to discuss whether, how and to what extent DAOs might comply. A policy position on the desirability and conditions under which DAOs could bring efficient, safe and stable innovations to the financial sector depends on the specificities of the individual DAOs, the potential applicable regulatory frameworks and the continuously evolving technical developments, as well as (inter)national guidelines and recommendations. This paper proposes that the establishment of regulatory frameworks on cryptoassets and crypto-asset services, such as the EU Markets in Crypto-Assets (MiCA) Regulation1 , may force DAOs to rethink their legal status, governance and operational models.
Keywords: F38; F39; G23; G32; K22; L22; L31; 330; DAO; DeFi; crypto; international financial policy; financing policy